The Effects of Unions on Profitability: Canadian Evidence - Maki, Dennis; Meredith, Lindsay (Relations industrielles / Industrial Relations, 1986)
Considering rates of return on capital, sales and assets, the evidence primarily but not unambigously supports a negative effect of unions on profitability. Whether this occurs only through effects on wages and labour productivity or through other channels as well is unclear.